Man from Music Mountain - Kane, Joseph, 1894-1975; Burbridge, Betty; Ward, Luci, 1907-1969; Autry, Gene, 1907-1998; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures Corp., 1938)
After the creation of Boulder Dam, a scheming land development company sets up operation in the deserted town of Gold River, Arizona. Convincing people that hydroelectric power will soon be coming to the area, parcels of land are sold to the unsuspecting investors. Gene tries to con the company into buying back the land, thus stopping the swindlers for good.
Originally released as a motion picture in 1938.
Gene Autry, Smiley Burnette, Carol Hughes, Sally Payne, Polly Jenkins and her Plowboys.
Cinematographer, Jack Marta; editor, Lester Orlebeck.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Swindlers and swindling -- Arizona -- Drama; Real estate development -- Arizona -- Drama; Western films; Feature films; Singing cowboy films; Internet videos; Streaming video